Recycling of waste gypsum boards to produce new drywalls and non-load bearing bricks - Ragab, Nada Khaled Fathy (AUC Knowledge Fountain, 2015)
Recycling of gypsum boards wastes is attractive but challenging at the same time. The quality and quantity of the waste is quite important. The amount of gypsum board waste is on the rise. Millions of tons of gypsum board waste are produced annually and only a small percentage of gypsum board waste is recycled. This waste threatens the environment in three main ways: producing Hydrogen Sulfide gas when dumped in a moist environment, increasing the use of landfills and depleting natural resources. Consequently, the United States is considering the prohibition of gypsum board waste partial or full dumping in landfills that contain biodegradable waste. Furthermore, the European Union has set some regulations to control the amount of disposable gypsum board waste in landfills. This study aims to recycle the waste gypsum boards in order to be used in feasible applications. It targets the possibility of utilizing gypsum board waste to produce new gypsum boards or to produce non-load bearing gypsum bricks. To meet this objective, flexural strength test was conducted for the gypsum boards samples. Moreover, standard tests such as compressive strength, flexural strength, water absorption and density, were performed on the gypsum bricks. Three phases of gypsum board waste were examined: unheated gypsum board waste ( ), gypsum board waste heated at 130 ( ), and heated gypsum at 250 ( ). The results of this research show that the highest flexural strength for gypsum boards was obtained when adding 0.5% of Zinc Sulfate to the heated gypsum board waste. The flexural strength of produced gypsum board exceeded that of the commercial gypsum board available in the market. Moreover, the results of the non-load bearing gypsum bricks demonstrate that the mechanical properties of these bricks meet the non-load bearing bricks standards. The recommended unheated gypsum brick mix is the one conducted using 0.3% of Zinc Sulfate. The compressive strength of the obtained sample exceeded the ASTM limit for concrete non-load bearing bricks as well as the National standard when tested after seven and fourteen days. The gypsum bricks that were conducted from mixing heated gypsum board waste with Zinc Sulfate did not meet the ASTM limit for concrete non-load bearing bricks. However, the compressive strength limit in the Egyptian Standard for non-load bearing cement bricks was achieved when adding 0.3% of Zinc Sulfate to the heated gypsum board waste. In conclusion, this study pinpoints the importance of recycling waste gypsum boards and provides the initiative of using this waste in suitable applications.